Nationwide practice and outcomes of endoscopic biliary drainage in resectable pancreatic head and periampullary cancer. Issue 2 (February 2021) - Latenstein, Anouk E.J.; Mackay, Tara M.; van Huijgevoort, Nadine C.M.; Bonsing, Bert A.; Bosscha, Koop; Hol, Lieke; Bruno, Marco J.; van Coolsen, Marielle M.E.; Festen, Sebastiaan; van Geenen, Erwin; Groot Koerkamp, Bas; Hemmink, Gerrit J.M.; et al.
Abstract: Background: Guidelines advise self-expanding metal stents (SEMS) over plastic stents in preoperative endoscopic biliary drainage (EBD) for malignant extrahepatic biliary obstruction. This study aims to assess nationwide practice and outcomes. Methods: Patients with pancreatic head and periampullary cancer who underwent EBD before pancreatoduodenectomy were included from the Dutch Pancreatic Cancer Audit (2017–2018). Multivariable logistic and linear regression models were performed. Results: In total, 575/1056 patients (62.0%) underwent preoperative EBD: 246 SEMS (42.8%) and 329 plastic stents (57.2%). EBD-related complications were comparable between the groups (44/246 (17.9%) vs. 64/329 (19.5%), p = 0.607), including pancreatitis (22/246 (8.9%) vs. 25/329 (7.6%), p = 0.387). EBD-related cholangitis was reduced after SEMS placement (10/246 (4.1%) vs. 32/329 (9.7%), p = 0.043), which was confirmed in multivariable analysis (OR 0.36 95%CI 0.15–0.87, p = 0.023). Major postoperative complications did not differ (58/246 (23.6%) vs. 90/329 (27.4%), p = 0.316), whereas postoperative pancreatic fistula (24/246 (9.8%) vs. 61/329 (18.5%), p = 0.004; OR 0.50 95%CI 0.27–0.94, p = 0.031) and hospital stay (14.0 days vs. 17.4 days, p = 0.005; B 2.86 95%CI −5.16 to −0.57, p = 0.014) were less after SEMS placement. Conclusion: This study found that preoperative EBD frequently involved plastic stents. SEMS seemed associated with lower risks of cholangitis and less postoperative pancreatic fistula, but without an increased pancreatitis risk.